LEGAL PROTECTION FOR THE PARTIES AS A PREVENTIVE AFFORT AGAINST DISPUTES IN HEALTH INSURANCE CLAIMS - Wibowo, Denny Ardhi; Sugianto, Fajar; Agustian, Sanggup Leonard (PRANATA HUKUM, 2025)
The central idea of this research is to propose an ius constituendum for legal protection of the parties involved in order to prevent disputes in health insurance claim settlements. This study is a normative legal research, employing both conceptual and statutory approaches, with the urgency of legal protection and the ius constituendum of legal protection in health insurance agreements serving as the primary legal issues. The findings reveal that the frequent occurrence of disputes, coupled with the fact that health insurance agreements are often adhesion contracts prone to abuse of circumstances, highlights the urgency of strengthening legal protection. Such protection should be enhanced particularly in the form of preventive legal measures, including regulations that prohibit unfair standard clauses in health insurance contracts and the establishment of a mandatory pre-contractual assessment before the insured signs the agreement. These elements can be regulated through Financial Services Authority Regulations (POJK).